El bioderecho en México: estado del arte y aplicaciones (2020)
Chapter analyze topies representative of the progress of biolaw in Mexico limited to biomedical law. In sorne cases, constitutional provisions, norms of sanitary, civil and criminal law are cited, especially those expressed in the different international documents, which the principles of bioethics have received as common denominator. Finally, the chapter addresses the interpretation of sorne laws by courts' judgments, which has expanded perspectives on biomedical matters in Mexico.